Production of bioethanol from multiple waste streams of rice milling. (November 2017) - Favaro, Lorenzo; Cagnin, Lorenzo; Basaglia, Marina; Pizzocchero, Valentino; van Zyl, Willem Heber; Casella, Sergio
Graphical abstract: Highlights: Rice milling by-products are promising feedstocks for bioethanol. Starch-rich residues were efficiently fermented by two engineered amylolytic yeast. Rice husk, composed by lignocellulose, was pre-treated with alkaline peroxide. Pre-treated husk was saccharified by commercial enzymes and fermented. Multiple rice by-products were co-processed to ethanol by amylolytic strains. Abstract: This work describes the feasibility of using rice milling by-products as feedstock for bioethanol. Starch-rich residues (rice bran, broken, unripe and discolored rice) were individually fermented (20% w/v) through Consolidated Bioprocessing by two industrial engineered yeast secreting fungal amylases. Rice husk (20% w/v), mainly composed by lignocellulose, was pre-treated at 55 °C with alkaline peroxide, saccharified through optimized dosages of commercial enzymes (Cellic® CTec2) and fermented by the recombinant strains. Finally, a blend of all the rice by-products, formulated as a mixture (20% w/v) according to their proportions at milling plants, were co-processed to ethanol by optimized pre-treatment, saccharification and fermentation by amylolytic strains. Fermenting efficiency for each by-product was high (above 88% of the theoretical) and further confirmed on the blend of residues (nearly 52 g/L ethanol). These results demonstrated for the first time that the co-conversion of multiple waste streams is a promising option for second generation ethanol production.